Bacillary hemoglobinuria in a cow - AMR, Correa; E, Edwards; A, de la Concha-Bermejillo; FA, Uzal (Brazilian Journal of Veterinary Pathology, 2023)
A 436 kg, 2-year-old, pregnant Angus cross cow was presented for necropsy with a history of sudden death during calving season. Two other heifers on the property recently had late term abortions with the calves having to be pulled out from the birth canal.